Evaluation of the Antithrombotic Activity of Acmella oleracea L. Flower Ethanol Extract - Tiaravista, Amanda Gita; Putri, Laras Widawaty; Nurrochmad, Arief; Widyarini, Sitarina; Fakhrudin, Nanang (Universitas Muhammadiyah Yogyakarta, 2023)
Acmella oleracea L. (hereinafter abbreviated as AOE) is one of the plants with the potential for antithrombosis, one of the deadliest cardiovascular diseases in Indonesia. The antithrombotic activity test on AOE leaf extract revealed that it could lyse blood clots. However, no information regarding the AOE flower as an antithrombosis is provided. This study, thus, aims to determine the chromatography profile and the antithrombotic activity of the AOE flower ethanol extract. To identify the AOE chemical profile, thin-layer chromatography was carried out. Antithrombotic testing was performed on male rats of the Sprague-Dawley strain. Then, the antithrombotic activity was tested using the FeCl3-induced rat method, with the observed parameter being total occlusion time. The test animals were also divided into six groups: normal, solvent (CMC-Na 0.9%), comparator drug (clopidogrel 8.67 mg/kg), and AOE (doses 125, 250, and 375 mg/kg). The data obtained were then analyzed statistically using Kruskal-Wallis, followed by Tukey's. The TLC profile results confirmed the presence of the alkaloid compound in AOE. The authors also found that AOE at doses of 125, 250, and 375 mg/kg significantly prolonged the occlusion time comparable to that of clopidogrel at 8.67 mg/kg (p > 0.05). This finding indicates that AOE has antithrombotic activity in FeCl3-induced rats.